2003
DOI: 10.1093/ndt/gfg020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T and malondialdehyde modified plasma lipids in haemodialysis patients

Abstract: This study confirms that the presence of cTnT predicts prognosis in ESRD. The presence of cTnT is linked to oxidative stress, inflammation and uraemia. The absence of specific findings on EKG and echocardiography points towards subclinical myocardial damage caused by endothelial disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
0
26
0
2
Order By: Relevance
“…These results thus may offer insight into the role of MPO-mediated oxidative stress in the progression of restrictive filling pattern and myocardial fibrosis. Previous outcome studies also have shown that other markers of oxidative stress, such as oxidized low-density lipoprotein, catecholamine-induced adrenolutin, and malondialdehyde from lipid peroxidation, are predictive of mortality (23)(24)(25). However, measurement of these biomarkers is technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…These results thus may offer insight into the role of MPO-mediated oxidative stress in the progression of restrictive filling pattern and myocardial fibrosis. Previous outcome studies also have shown that other markers of oxidative stress, such as oxidized low-density lipoprotein, catecholamine-induced adrenolutin, and malondialdehyde from lipid peroxidation, are predictive of mortality (23)(24)(25). However, measurement of these biomarkers is technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that cardiovascular diseases have also been related to free radical-mediated mechanisms and to lipid peroxidation, along with the fact that they are a major cause of mortality and morbidity in hemodialysis patients. Study reported by Scott et al 30 demonstrated that plasma MDA values were elevated in hemodialysis patients and higher in hemodialysis patients with cardiovascular complications.…”
Section: Lipid Peroxidation and Mdamentioning
confidence: 91%
“…Malondialdehyde (MDA) is one of the better-known secondary products of lipid peroxidation, and it can be used in biomaterials as an indicator of cell membrane injury [3], being that oxidative stress has been implicated in the pathogenesis of various diseases, including diabetes [4], cancer [5], atherosclerosis [6,4], renal [7] and Alzheimer diseases [8].…”
Section: Introductionmentioning
confidence: 99%